Podgotovka legkoatleta-sprintera: strategija, planirovanie, tehnologii - Borzov, V. (Science in Olympic Sport, 2019)
Objective. To generalize the long-term training experience on the material of sprinting.Methods. Analysis and generalization of data of scientific and methodological literature, generalization of own experience of preparation, autoexperiment, methods of statistical analysis. Results. The basic preparation of Olympic champion Valeriy Borsov being the foundation for development of various motor qualities required by a sprinter, conducted under the guidance of the thoughtful, creative teacher Boris Ivanovich Voitas is considered. Examples of various training means allowing to master a wide arsenal of movements and the optimal technique for their execution are given. Examples of the content of the annual preparation in youth sports, divided into six stages, are presented. The experience of transition from youth to adult sport under the leadership of Valentin Petrovsky, who wisely tutored Valery Borzov from the negative consequences of a hasty ascent to a high international - Olympic - level, is reflected. The modes of loads (exercises)/rest alternation are considered, which allows to optimize the process of sports training and make it manageable. The system of long-term planning of sports training is revealed: regulation of body vital activity and its functional capacities for demonstration of the highest sports result at the moment of the major competitions is scientifically substantiated. The strategy of planning sports training in the four-year Olympic preparation cycles (1968-1972) for the Games of the XX Olympiad 1972 in Munich and the Games of the XXI Olympiad 1976 in Montreal is presented. Training means of different preferential orientation are described in detail. A characteristic of training process individual features is given. The system of control, tactical and mental preparation, means of sprinter recovery are highlighted. Conclusion. The strategies, planning, technologies of training track and field athletes, and the preparation for the major com-petitions of the four-year cycle, which are reflected in the article on the example of sprint running, may be useful for track and field sprinters and their coaches for creative training planning.